(untitled) (Світ фінансів, 2017)
Гварлиани Т. E., Осинова М. Г. К вопросу о природе налогового консультирования. Рассмотрены теоретические основы налогового консультирования. Проанализировано становление налогового консалтинга и подходы к определению понятия “налоговое консультирование”. Раскрыто правовое регулирование налогового консалтинга в России. Gvarliani T., Osinova M. About essence of tax consulting. The theoretical bases of tax consulting are considered. The formation of tax consulting and the approaches to determination of concept of tax consulting are analysed. The legal regulation of tax consulting in Russian Federation is revealed.